2010
DOI: 10.1002/cphc.201000461
|View full text |Cite
|
Sign up to set email alerts
|

Surface Chemical Properties of Eutectic and Frozen NaCl Solutions Probed by XPS and NEXAFS

Abstract: We study the surface of sodium chloride-water mixtures above, at, and below the eutectic temperature using X-ray photoelectron spectroscopy (XPS) and electron-yield near-edge X-ray absorption fine structure (NEXAFS) spectroscopy. The NaCl frozen solutions are mimicking sea-salt deposits in ice or snow. Sea-salt particles emitted from the oceans are a major contributor to the global aerosol burden and can act as a catalyst for heterogeneous chemistry or as cloud condensation nuclei. The nature of halogen ions a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
40
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 31 publications
5
40
0
Order By: Relevance
“…These results represent the starting point for an improved understanding of the structure of eutectic and sub-eutectic frozen salt solutions in presence of ice (high relative humidity), and in the hydrate stability domain of the phase diagram (low relative humidity). Moreover, the Cl K-edge measurements complement and extend previously reported measurements at the O K-edge NEXAFS for the same system [52], which is sensitive to the hydrogen bonding environment of the water molecules. However, compared to the oxygen K-edge, the higher kinetic energy of the chlorine K-edge Auger electron corresponds to an increased probing depth of about 2-8 nm, and, therefore, to a much more bulk-sensitive measurement.…”
Section: Phase Changes Of Nacl-water Binary Systemssupporting
confidence: 83%
See 1 more Smart Citation
“…These results represent the starting point for an improved understanding of the structure of eutectic and sub-eutectic frozen salt solutions in presence of ice (high relative humidity), and in the hydrate stability domain of the phase diagram (low relative humidity). Moreover, the Cl K-edge measurements complement and extend previously reported measurements at the O K-edge NEXAFS for the same system [52], which is sensitive to the hydrogen bonding environment of the water molecules. However, compared to the oxygen K-edge, the higher kinetic energy of the chlorine K-edge Auger electron corresponds to an increased probing depth of about 2-8 nm, and, therefore, to a much more bulk-sensitive measurement.…”
Section: Phase Changes Of Nacl-water Binary Systemssupporting
confidence: 83%
“…In the following, we show how NEXAFS spectroscopy at the Cl K-edge can be highly informative on the nature of the NaCl structure in NaCl-water binary systems. Using XPS and NEXAFS spectroscopies of the O 1s core level and O K-edge, respectively, we previously showed that these systems follow the phase rules at the airice interface [52]. This finding contrasts some earlier observations, where the presence of liquid-like Cl below the eutectic point of bulk solutions [53] was postulated (see Ref.…”
Section: Phase Changes Of Nacl-water Binary Systemsmentioning
confidence: 61%
“…Wren and Donaldson (2011) reported only a minor increase in nitrate concentration at the ice surface and suggested that nitrate might be favourably incorporated into pockets or grain boundaries inside bulk ice at 258-268 K. A similar tendency of nitrite to be captured in liquid reservoirs inside growing ice was suggested earlier (Takenaka et al, 1996). Using surfacesensitive spectroscopy Křepelová et al (2010a) showed that frozen solutions of NaCl above the eutectic exhibited a composition on the ice surface consistent with the phase diagram of the bulk solution. This is in agreement with earlier work by Döppenschmidt and Butt (2000) where solid NaCl crystals were identified at the ice surface at temperatures below the eutectic using AFM.…”
Section: Solutes During the Freezing Processmentioning
confidence: 61%
“…Freezing of emulsions that resemble water droplets in the atmosphere can be kinetically hindered so that a meta-stable liquid phase exists well below the eutectic temperature (Koop et al, 2000;Bogdan, 2010). Using surface-sensitive, synchrotron-based X-ray spectroscopy, Křepelová et al (2010a) found no evidence for liquid on the surface of frozen solutions of NaCl below the eutectic. This technique probes the local, chemical environment of the chloride anions and does not rely on assumptions based on bulk properties to derive conclusions about the physical state of the probe.…”
Section: Below the Eutectic Compositionmentioning
confidence: 99%
See 1 more Smart Citation